Pengaruh Keterampilan Komunikasi Interpersonal Dan Fasilitas Belajar Terhadap Motivasi Belajar SiswaDi Smp N 2 Ngemplak - Hikari, Avita Fatwa, Dr. Ahmad Muhibbin, M. Si (2017)
This research aimed to know the influence of interpersonal communication skills of teacher and learning facilities to the learning motivation of students of Junior High School 2 of Ngemplak. Population taken in this research was 689 students of Junior High School 2 of Ngemplak. Samples were collected using technique of proportional quota random sampling involved total samples of 30 students. Data validity technique in this research applied the method of moment product rough number and halved. Test of normality used One-Sample Kolmogorov-Smirnov Test and data reliability testused Cronbach Alpha formula. Analysis used in this research was regression analysis with the formula of two predictor regression. The result of the study showed that interpersonal communication skills and learning facility had significant influence to the students' learning motivation. However, the influence given through interpersonal communication skills and learning facilities to the learning motivation of the students of Junior High School 2 of Ngemplak was only 31.6%, while the rest (68.4%) was influenced by other variables which was unreachable to the researcher.